Japanese Rinzai Zen Buddhism : Myōshinji, a living religion - Borup, Jørn. (Numen Book Series, 2008)
Zen Buddhist ideas and practices in many ways are unique within the study of religion, and artists, poets and Buddhists practitioners worldwide have found inspiration from this tradition. Until recent years, representations of Zen Buddhism have focussed almost entirely on philosophical, historical or "spiritual" aspects. This book investigates the contemporary living reality of the largest Japanese Rinzai Zen Buddhist group, Myōshinji. Drawing on textual studies and ethnographic fieldwork, Jørn Borup analyses how its practitioners use and understand their religion, how they practice their religiosity and how different kinds of Zen Buddhists (monks, nuns, priest, lay people) interact and define themselves within the religious organization. Japanese Rinzai Zen Buddhism portrays a living Zen Buddhism being both uniquely interesting and interestingly typical for common Buddhist and Japanese religiosity.